Building resilience: India’s network of radiation emergency response centers - Anirudh Chandra; Shashank Saindane; R. K. B. Yadav; Probal Chaudhury; Dinesh Kumar Aswal (Radiation Protection and Environment)
India’s expanding nuclear energy program and the increased use of radiation technologies are essential for fulfilling its energy needs and delivering societal benefits. However, this growth also heightens the risk of radiation hazards, necessitating a robust radiation emergency response system. Currently, the Department of Atomic Energy operates 25 Radiation Emergency Response Centers (RERCs) across the country, which provide technical support to responder agencies during nuclear and radiological emergencies at both nuclear facilities and in public spaces. This paper outlines the role and operational elements of RERCs within the emergency preparedness and response framework, drawing on a review of various national response and regulatory documents, as well as discussions with national radiation emergency response experts. This work not only highlights the domestic capabilities of India’s RERC network but also serves as a valuable resource for policymakers and technocrats striving to strengthen and enhance the country’s radiation emergency response infrastructure.